CITA RASA TEH BOTOL SOSRO TERCERMIN PADA PROMOSI PENJUALANNYA - Bayquni, Bayquni (Universitas Prof. Dr. Moestopo (Beragama), 2011)
Companies must have a marketing strategy to promote or market a product, in order to attract the attention of consumers. One strategy used by companies in marketing their products, through advertising. Advertising is the most effective marketing medium. Advertising can drive purchasing decisions. Therefore the content of advertisements should be clear and understandable to consumers. An advertisement should be able to represent the product being advertised .. Effective advertising can influence buying decisions. This means that advertising has become a marketing tool to assist in establishing effective communication between the company and its customers to penetrate the increasingly fierce market competition.In the effect between advertising and sales promotion with this then, can drive the purchase decision, need to do a variety of efforts to create a strategy to create customer satisfaction by analyzing the needs and desires of consumers to the products on offer. With this strategy by presenting the companys thinking about a different product with other products, as well as having a high quality to strengthen its position in promoting a product, then the consumer makes such products as the main option.Many options that are promoted or beverage products offered through advertising by introducing the benefits of the drink product. With so many choices beverage products, increasing competition that drives the purchase decision in determining the sales promotion of such products. One of the beverage products that have achieved market share, The Botol Sosro issued by PT. SINAR SOSRO.